ANALYSIS OF CRITICAL THINKING PROCESS OF BLIND STUDENTS TO SOLVING FLAT BUILDING MATERIALS - Sofyan Adian Mukti; Sugiman Sugiman (UNIVERSITAS MUHAMMADIYAH METRO, 2023)
Education is an element that is very important for human survival, with the regulated it in a Law of the Republic of Indonesia article 15 of Law no. 20 of 2003 regarding the National Education System this type of education is for children with special needs.Education with special needs requires attention in its application, children with low vision special needs experience many difficulties in learning and applying critical thinking. This study aims to improve the quality of learning Mathematics and improve students' critical thinking skills. Critical thinking is needed in learning, including for blind students. So that critical thinking skills are needed in the learning process so that blind students can understand the material and solve problems well so that further research is needed. The research method used is descriptive qualitative, with the object of research being blind students at SLBN Ungaran The results of this study indicate the difficulty of blind students in answering flat shape questions based on mathematical critical thinking skills. Several factors cause including: (1). Students' difficulties in understanding the types of flat shapes; (2). When doing calculations, students need help understanding the shape of a flat shape so that the calculations and work processes carried out are not quite right. This Problem happens because students still need help understanding, analyzing, and identifying the purpose of the questions; (3). Student's difficulties in connecting the relationship between the concept and the Problem so that students have difficulty in determining the completion strategy.Pendidikan merupakan elemen yang sangatlah penting bagi kelangsungan hidup manusia, Diatur dalam Undang undang Republik Indonesia pasal 15 UU No. 20 tahun 2003 mengenai Sistem Pendidikan Nasional bahwa jenis pendidikan bagi Anak berkebutuhan khusus. Pendidikan berkebutuhan khusus memerluka perhatian dalam penerapan nya, anak berkebutuhan khusus low vision banyak mengalami kesulitan dalam belajar dan menerapkan berpikir kritis, penelitian ini bertujuan untuk meningkatkan kualitas pembelajaran Matematika, meningkatkan keterampilan berpikir kritis siswa. Proses berpikir kritis sangat dibutuhkan dalam pembelajaran tidak terkecuali untuk peserta didik tunanetra. Sehingga dibutuhkan kemampuan berpikir kritis yang dalam proses pembelajaran agar peserta didik tunanetra bisa memahami materi dan menyelesaikan soal dengan baik sehingga perlu dilakukan penelitian lebih lanjut. Metode penelitian yang digunakan adalah kualitatif deskriptif, dengan obyek penelitian siswa tunanetra di SLBN Ungaran. Hasil penelitian ini menunjukkan kesulitan siswa tunanetra dalam menjawab soal bangun datar berdasarkan kemampuan berpikir kritis matematis. menyelesaikan permasalahan disebabkan oleh beberapa faktor diantaranya adalah: (1). Kesulitan siswa dalam memahami jenis bangun datar; (2). Saat melakukan perhitungan siswa kesulitan dalam memahami bentuk bangun datar sehingga perhitungan dan proses pengerjaan yang dilakukan kurang tepat. Hal tersebut terjadi karena siswa masih kesulitan dalam memahami, menganalisis, dan mengidentifikasi tujuan soal; (3). Kesulitan siswa menghubungkan keterkaitan konsep dengan soal sehingga siswa kesulitan dalam menentukan strategi penyelesaian.